Copper toxicity and deficiency: the vicious cycle at the core of protein aggregation in ALS - Min, Jin-Hong; Sarlus, Heela; Harris, Robert A. (Frontiers in Molecular Neuroscience, 2024)
The pathophysiology of ALS involves many signs of a disruption in copper homeostasis, with both excess free levels and functional deficiency likely occurring simultaneously. This is crucial, as many important physiological functions are performed by cuproenzymes. While it is unsurprising that many ALS symptoms are related to signs of copper deficiency, resulting in vascular, antioxidant system and mitochondrial oxidative respiration deficiencies, there are also signs of copper toxicity such as ROS generation and enhanced protein aggregation. We discuss how copper also plays a key role in proteostasis and interacts either directly or indirectly with many of the key aggregate-prone proteins implicated in ALS, such as TDP-43, C9ORF72, SOD1 and FUS as well as the effect of their aggregation on copper homeostasis. We suggest that loss of cuproprotein function is at the core of ALS pathology, a condition that is driven by a combination of unbound copper and ROS that can either initiate and/or accelerate protein aggregation. This could trigger a positive feedback cycle whereby protein aggregates trigger the aggregation of other proteins in a chain reaction that eventually captures elements of the proteostatic mechanisms in place to counteract them. The end result is an abundance of aggregated non-functional cuproproteins and chaperones alongside depleted intracellular copper stores, resulting in a general lack of cuproenzyme function. We then discuss the possible aetiology of ALS and illustrate how strong risk factors including environmental toxins such as BMAA and heavy metals can functionally behave to promote protein aggregation and disturb copper metabolism that likely drives this vicious cycle in sporadic ALS. From this synthesis, we propose restoration of copper balance using copper delivery agents in combination with chaperones/chaperone mimetics, perhaps in conjunction with the neuroprotective amino acid serine, as a promising strategy in the treatment of this incurable disease.